The Effect of the Duolingo App to Improve Vocabulary Mastery Among Gen-Z In an English Course Program - Ilham Ramdhani; Hariyanto Subiyantoro (MASI Mandiri Edukasi, 2025)
This study aims to examine the effect of Duolingo on improving vocabulary mastery among Generation Z students in an English course program. This study employed an experimental design with a one-group pre-test and post-test to investigate the effectiveness of using the Duolingo application in enhancing vocabulary learning. Thirty-nine elementary school students aged 7–12 participated in the program, where Duolingo was integrated into classroom activities for five months. Data were collected through vocabulary tests, observations, and interviews. The results revealed a significant improvement in students’ vocabulary mastery, with the mean score increasing from 54.10 in the pre-test to 85.77 in the post-test. Statistical analysis using a paired t-test confirmed a highly significant difference (t = 10.64, p < 0.001), indicating that the Duolingo application effectively enhanced vocabulary acquisition. In addition, qualitative findings showed that students responded positively to using Duolingo, reporting increased motivation and engagement during learning. These findings suggest that mobile-assisted language learning (MALL) tools such as Duolingo can be effective instructional media for young learners, particularly in non-formal educational settings. The study contributes to technology-based pedagogy by highlighting the potential of gamified applications to foster vocabulary mastery and learner motivation.